Providers' responses to the patients' rights charter in South Africa: a case study in policy implementation - Raphaely, Nika Thandiwe (My University, 2010)
Abstract The Patient Rights’ Charter is one of several progressive health policies in South Africa with disappointing implementation in practice. Barriers to implementation have already been described. Policy analysis theory and empirical studies suggest that power and resistance may contribute to implementors’ responses to policies. This secondary analysis of existing semistructured interviews with health providers in Limpopo explicitly examined the influence of power and resistance on their implementation of the Patients’ Rights Charter. Open coding yielded themes of implementation experience, to which a deductive analysis applied a heuristic framework, derived from the literature, to examine power and resistance. The critical importance of implementors in translating policy into practice, and of discursive manifestations of power, were reiterated. Resonances in the data of the functionalist ‘sick role’ brought together surveillance, expert knowledge and the loss of health workers’ influential voice, in a way not previously discussed. Implications for future management strategies are considered.
Thesis (M.P.H.), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: patient rights charter; case study